2017
DOI: 10.1016/j.conbuildmat.2017.08.083
|View full text |Cite
|
Sign up to set email alerts
|

Ni-Ti SMA bars behaviour under compression

Abstract: SMA (Shape Memory Alloys) is a type of material suitable for using in civil engineering as concrete rein-47 forcement because of their shape memory effect or superelasticity and their high ductility and damping 48 capacity. However, Ni-Ti alloys Young modulus could be 3 or 4 times lower than steel (200 GPa) depend-49 ing on the composition and thermal treatment, which can cause the instability of compressed bars. The 50 main objective of this work is to provide a modified constitutive model of SMA bars, partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 48 publications
1
19
0
Order By: Relevance
“…Finally, the bar reached a second instability point and the supported load decreased due to second-order effects. Pereiro-Barceló and Bonet [4] tested 12 mm-diameter bars and also found two instability points in the least slender specimens. They proposed a method to modify the constitutive equation under compression of SMA bars to consider buckling according to on an analytical procedure and experimental results.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…Finally, the bar reached a second instability point and the supported load decreased due to second-order effects. Pereiro-Barceló and Bonet [4] tested 12 mm-diameter bars and also found two instability points in the least slender specimens. They proposed a method to modify the constitutive equation under compression of SMA bars to consider buckling according to on an analytical procedure and experimental results.…”
Section: Introductionmentioning
confidence: 92%
“…This behaviour is caused because the reinforcement area increases when the bar is compressed due to the Poisson effect. In order to take this difference into account in behaviour, and in order to keep considering the same area in tension and compression from the engineering point of view, Dodd and Restrepo-Posada [49] proposed the following expressions to transform the constitutive relation under tension (r À e) to compression ðr 00 À e 00 Þ: Bonet [4] analysed inelastic buckling behaviour of these bars outside concrete with various slenderness ratios.…”
Section: Specimensmentioning
confidence: 99%
See 1 more Smart Citation
“…The finite element model was validated with experimental results on circular columns in previous research [45]. The same boundary conditions, applied loads, imposed displacements, material type, and element type were employed.…”
Section: Finite Element Model Descriptionmentioning
confidence: 99%
“…(8) Pereiro-Barceló and Bonet proposed a new analytical model of the buckling/post-buckling behavior of Ni-Ti SMA bars. (9) These studies found that Ti-Ni SMA memorized to a straight shape shows negative or quasizero stiffness during post-buckling deformation. Since the deformation of SMA elements can be recovered during the unloading process by superelastic behavior, the negative or quasizero stiffness characteristic can be used repeatedly.…”
Section: Introductionmentioning
confidence: 97%